Social Solidarity Entrepreneurship: Salinas Group of Ecuador (1990-2020) - Guerrero Carrasco, Martha; Vanoni, Giuseppe; Omaña, Alfonso (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Social and solidarity economy organizations gain relevance and importance in a country like Ecuador. for this reason, this paper explains, through a structured strategic analysis model, how gruppo Salinerito has established as an organization that involves the whole community of Salinas de Guaranda, in the socially responsible production and commercialization of dairy products to provide quality of life to the population.